Précis of cognitive gadgets: the cultural evolution of thinking - Heyes, C (Cambridge University Press, 2018)
Cognitive gadgets are distinctively human neurocognitive mechanisms – such as imitation, mindreading, and language - that have been shaped by cultural rather than genetic evolution. New gadgets emerge, not by genetic mutation, but by innovations in cognitive development; they are specialised cognitive mechanisms built by general cognitive mechanisms using information from the sociocultural environment. Innovations are passed on to subsequent generations, not by DNA replication, but through social learning: people with a new cognitive mechanism pass it on to others through social interaction. And some of the new mechanisms, like literacy, have spread through human populations, while others have died out, because the holders had more students, not just more babies. The cognitive gadgets hypothesis is developed through four case studies, drawing on evidence from comparative and developmental psychology, experimental psychology and cognitive neuroscience. The framework employed, cultural evolutionary psychology, a descendant of evolutionary psychology and cultural evolutionary theory, addresses parallel issues across the cognitive and behavioural sciences. In common with evo-devo and the extended evolutionary synthesis, cultural evolutionary psychology underlines the importance of developmental processes and environmental factors in the emergence of human cognition. In common with computational approaches (deep learning, predictive coding, hierarchical reinforcement learning, causal modelling) it emphasises the power of general-purpose mechanisms of learning. However, cultural evolutionary psychology also challenges use of the behavioural gambit in economics and behavioral ecology, and rejects the view that human minds are composed of ‘innate modules’ or ‘cognitive instincts’.